2021
DOI: 10.1186/s13054-021-03623-4
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus ventilator-associated pneumonia in patients with COVID-19: clinical features and potential inference with lung dysbiosis

Abstract: Background Hospitalized patients with COVID-19 admitted to the intensive care unit (ICU) and requiring mechanical ventilation are at risk of ventilator-associated bacterial infections secondary to SARS-CoV-2 infection. Our study aimed to investigate clinical features of Staphylococcus aureus ventilator-associated pneumonia (SA-VAP) and, if bronchoalveolar lavage samples were available, lung bacterial community features in ICU patients with or without COVID-19. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 58 publications
4
36
0
5
Order By: Relevance
“…In Staphylococcus aureus blood isolates from patients hospitalized in the wards, significant changes in the slope of non-susceptibility to oxacillin between the two study periods was observed, which is consistent with the literature [ 27 , 65 , 74 ]. Of note, the decreasing trend for oxacillin non-susceptibility during the pre-pandemic period was followed by an increasing one.…”
Section: Discussionsupporting
confidence: 91%
“…In Staphylococcus aureus blood isolates from patients hospitalized in the wards, significant changes in the slope of non-susceptibility to oxacillin between the two study periods was observed, which is consistent with the literature [ 27 , 65 , 74 ]. Of note, the decreasing trend for oxacillin non-susceptibility during the pre-pandemic period was followed by an increasing one.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, excluding coinfections, emerging data confirmed the importance of MRSA as a potential agent of secondary infections, including ventilator-associated pneumonia (VAP) in subjects hospitalized in ICU for SARS-CoV-2 respiratory failure [29] and severe bloodstream infections [30], significantly increasing the overall risk of mortality. In fact, a dramatically high 14-day and 30-day mortality (54.8% and 66.7%, respectively) was documented in a recently published case series of S. aureus bloodstream infections [31].…”
Section: Resultsmentioning
confidence: 95%
“…In New Jersey, during a peak of COVID-19 cases in April 2020, Perez et al reported several unintentional changes in standard infection prevention and control (IPC) practices, which included a temporary discontinuation of appropriate PPE use, environmental cleaning and prolonged use of ventilator circuits and suctioning catheters [98]. Furthermore, in Italy, in a perspective case-control study conducted by De Pascale et al on mechanically ventilated patients, the proportion of ventilator associated pneumonia due to methicillin-resistant vs. methicillin susceptible S. aureus was significantly higher for COVID-19 patients (65.0% vs. 27.5%; p < 0.01) vs. non-COVID-19 patients, suggesting a higher rate of MRSA colonization/environmental contamination in COVID-19 ICUs [29].…”
Section: Discussion Disruption Of Infection Control Measures and Antimicrobial Stewardship In Covid Icusmentioning
confidence: 92%
“…Of these 28 included studies, 22 were case reports (describing single patients with individual data), two were case series (describing 7–42 patients with aggregate data), and four were cohort studies (describing 4–40 patients with aggregate data). Countries of study publication included the United States (n = 7) [ 7 , 9 , 21 25 ], Italy (n = 7) [ 26 32 ], Japan (n = 2) [ 33 , 34 ], Iran (n = 2) [ 35 , 36 ], the United Kingdom (n = 2) [ 37 , 38 ], Spain (n = 2) [ 39 , 40 ], Bahrain (n = 1) [ 41 ], China (n = 1) [ 42 ], France (n = 1) [ 43 ], the Philippines (n = 1) [ 44 ], Korea (n = 1) [ 45 ], and Canada (n = 1) [ 46 ], with publication dates ranging from April 15, 2020 to June 16, 2021. Table 1 describes the characteristics of these included studies and available information on their respective patient demographics in detail.…”
Section: Resultsmentioning
confidence: 99%